2021
DOI: 10.1042/bcj20200653
|View full text |Cite
|
Sign up to set email alerts
|

Tracking biochemical changes induced by iron loading in AML12 cells with synchrotron live cell, time-lapse infrared microscopy

Abstract: Hepatocytes are essential for maintaining homeostasis of iron and lipid metabolism in mammals. Dysregulation of either iron or lipids has been linked with serious health consequences, including non- alcoholic fatty liver disease (NAFLD). Considered the hepatic manifestation of metabolic syndrome, NAFLD is characterised by dysregulated lipid metabolism leading to a lipid storage phenotype. Mild to moderate increases in hepatic iron have been observed in approximately 30% of individuals with NAFLD; however, dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…ACSL6 is more highly expressed in NASH than HOC, although it has previously been reported in several cell lines, including the hepatoma cell line HepG2, not to be associated with ferroptosis ( 67 ). Increases in acyl-CoA synthetases are consistent with our previous findings in AML12 mouse hepatocytes that lipid accumulation occurs within 16 hours of iron loading and continues to increase over the subsequent 8 hours ( 70 ). However, the mechanism behind differential regulation of three ACSL isoforms, all of which are associated with cell death pathways, remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…ACSL6 is more highly expressed in NASH than HOC, although it has previously been reported in several cell lines, including the hepatoma cell line HepG2, not to be associated with ferroptosis ( 67 ). Increases in acyl-CoA synthetases are consistent with our previous findings in AML12 mouse hepatocytes that lipid accumulation occurs within 16 hours of iron loading and continues to increase over the subsequent 8 hours ( 70 ). However, the mechanism behind differential regulation of three ACSL isoforms, all of which are associated with cell death pathways, remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Iron has been shown to have a role in altering hepatic equilibrium between lipid uptake, synthesis, oxidation, and export, leading to lipid accumulation due to impairment of mitochondrial β-oxidation gene and protein expression (35,36), and dysregulated lipid synthesis (37)(38)(39). In mice, we demonstrated that iron loading increased the expression of genes involved in the biosynthesis of cholesterol (40) and increased lipid polyunsaturation in a hepatic cell line, potentially increasing susceptibility to oxidative stress (41). This review focuses on the role of iron loading in the dysregulation of lipid metabolism and the consequences for the development and progression of NAFLD.…”
Section: Iron In the Context Of Nafldmentioning
confidence: 72%
“…ELOVL2 elongates C20:4 to C22:4 and C20:5 to C22:5 and protein levels were increased in rats fed with a high fat diet plus ferric citrate, although no change in activity was evident (112). Nevertheless, increases in the ELOVL family of proteins were consistent with increases in synthesis of longer-chain fatty acids and may explain the increase in fatty acid chain length observed in AML12 cells incubated with ferric ammonium citrate (41). Elovl3 and Elovl5, which are believed to be involved in the elongation of multiple length fatty acids, exhibited reduced gene expression in mice fed with 2% carbonyl iron (38,71).…”
Section: De Novo Lipid Synthesismentioning
confidence: 85%
“…In recent decades, SR-FTIR-based microspectroscopy and imaging have been widely applied in stem cell-related research. A phenotypic screening approach revealed that the chemical information in single cells could be further studied [ 13 , 53 ]. SR-FTIR was applied here to identify changes related to molecular biomarkers in cancer stem cells.…”
Section: Future Directionsmentioning
confidence: 99%